Alcohol Abuse and Illegal Drug Use among Los Angeles County Trauma Patients: Prevalence and Evaluation of Single Item Screener - Ramchand, Rajeev (2009)
BACKGROUND: The misuse of alcohol and illicit drugs is implicated with injury and repeat injury. Admission to a trauma center provides an opportunity to identify patients with substance use problems and initiate intervention and prevention strategies. To facilitate the identification of trauma patients with substance use problems, we studied alcohol abuse and illegal substance use patterns in a large cohort of urban trauma patients, identified correlates of alcohol abuse, and assessed the utility of a single item binge-drinking screener for identifying patients with past 12-month substance use problems. METHODS: Between February 2004 and August 2006, 677 patients from four large trauma centers in Los Angeles (LA) County were interviewed. The sample was broadly representative of the entire LA County trauma center patient population. RESULTS: 24% of patients met criteria for alcohol abuse and 15% reported using an illegal drug other than marijuana in the past 12-months. Male gender, assaultive injury, peritrauma substance use, and history of binge drinking were prominent risk factors. A single-item binge drinking screen correctly identified alcohol abuse status in 76% of all patients; the screen also performed moderately well in discriminating between those who had or had not used illegal drugs in the past 12-months, with sensitivity estimates reaching 0.79 and specificity estimates reaching 0.74. CONCLUSIONS: A large proportion of urban trauma patients abuse alcohol and use illegal drugs. Distinct sociodemographic and substance use history may indicate underlying risky behaviors. Interventions and injury prevention programs need to address these causal behaviors to reduce injury morbidity and recidivism. In the busy trauma care setting, a one-item screener could be helpful in identifying patients who would benefit from more thorough assessment and possible brief intervention.